Constraining Mass of M31 Combing Kinematics of Stars, Planetary Nebulae and Globular clusters. (1st August 2022) - Yuan, Sunshun; Zhu, Ling; Liu, Cheng; Qu, Han; Fan, Zhou
Abstract: We construct a multiple-population discrete axisymmetric Jeans model for the Andromeda (M31) galaxy, considering three populations of kinematic tracers: 48 supergiants and 721 planetary nebulae (PNe) in the bulge and disk regions, 554 globular clusters extending to ∼30 kpc, and halo stars extending to ∼150 kpc of the galaxy. The three populations of tracers are organized in the same gravitational potential, while each population is allowed to have its own spatial distribution, rotation, and internal velocity anisotropy. The gravitational potential is a combination of stellar mass and a generalized NFW dark matter halo. We created two sets of models, one with a cusped dark matter halo and one with a cored dark matter halo. Both the cusped and cored model fit kinematics of all the three populations well, but the cored model is not preferred due to a too high concentration compared to that predicted from cosmological simulations. With a cusped dark matter halo, we obtained total stellar mass of 1.0 ± 0.1 × 10 11 M ⊙, dark matter halo virial mass of M 200 = 7.0 ± 0.9 × 10 11 M ⊙, virial radius of r 200 = 184 ± 4 kpc, and concentration of c = 20 ± 4. The mass of M31 we obtained is at the lower side of the allowed ranges in the literature and consistent with the previous results obtained from the H i rotation curve and PNe kinematics. Velocity dispersion profile of the outer stellar halo is important in constraining the total mass while it is still largely uncertain. Further proper motion of bright sources from Gaia or the Chinese Space Station Telescope might help on improving the data and lead to stronger constraints on the total mass of M31.